Gambaran aktivitas dan stabilitas antioksidan ekstrak beras hitam (Oryza sativa L.) kultivar Enrekang Sulawesi Selatan - Tan, Pricilia; Mayulu, Nelly; Kawengian, Shirley (Universitas Sam Ratulangi, 2016)
Abstract: Rice is the main type of food that is very essential to the people of Asia, especially in Indonesia. Color pigments, which are located on the outer layer of black rice paddy, have been reported to contain a mixture of anthocyanin compounds. Anthocyanin compounds act as antioxidants and free radical catchers, which serve to prevent some degenerative diseases. Black rice contains a nutritional value that is superior to other types of rice. It includes high content of protein, vitamins and minerals although there are distinct varieties depending on the location of production. This research has intended to determine the description of the activity and stability of the antioxidant from black rice extract (Oryza sativa L.) cultivars in Enrekang, South Sulawesi at 100 degrees Celsius heating with the periods of 0, 10, 20 and 30 minutes, and the antioxidant activity has been tested using DPPH and FRAP methods. Based on the results of the research using DPPH method, it was discovered that the activity of radical scavengers increased by the effect of the temperature from extracts of the black rice cultivar in Enrekang heated for 0, 10, 20, and 30 minutes at a temperature of 100 Â° C and the antioxidant activity of the extracts of the black rice was relatively stable against heating that was tested using FRAP.Keywords: black rice, antioxidants, DPPH, FRAPAbstrak: Beras merupakan jenis pangan utama yang penting bagi masyarakat di Asia, terutama di Indonesia. Pigmen warna yang terletak pada lapisan luar padi dari beras hitam telah dilaporkan mengandung campuran senyawa antosianin, senyawa antosianin berfungsi sebagai antioksidan dan penangkap radikal bebas, sehingga berperan untuk mencegah terjadinya beberapa penyakit degeneratif. Beras hitam memiliki kandungan nilai gizi yang lebih unggul dari beras jenis lainya. Seperti kandungan protein yang tinggi, vitamin dan mineral. Meskipun terdapat perbedaan varietas tergantung pada lokasi produksinya. Penelitian ini bertujuan untuk mengetahui gambaran aktivitas dan stabilitas antioksidan dari ekstrak beras hitam (Oryza sativa L.) kultivar Enrekang, Sulawesi Selatan pada pemanasan 100oc dengan lama pemanasan 0, 10, 20, dan 30 menit dan diuji aktivitas antioksidan menggunakan metode DPPH dan FRAP. Berdasarkan hasil penelitian menggunakan metode DPPH, didapatkan bahwa aktivitas penangkal radikal bebas meningkat dengan efek pemanasan pada ekstrak beras hitam (Oryza sativa L.) kultivar Enrekang Sulawesi Selatan dengan pemanasan 0, 10, 20, dan 30 menit pada suhu 100oC. Dan aktivitas antioksidan pada ekstrak beras hitam relative stabil terhadap pemanasan yang diuji menggunakan metode FRAP.Kata kunci: beras hitam, antioksidan, DPPH, FRAP